Islamic Perspective In Consumers Protecting Of E-Commerce Transactions In Indonesia - Andreas, Ricco; Andini, Pingkan Retno; Rulanda, Sija Putra (Universitas Islam Negeri Raden Intan Lampung, 2019)
ABSTRACTElectronic transaction mechanism in Indonesia often cause losses to consumers. Consumer protection should be applied in all conditions in transactions,both in conventional and manual transactions.But with the development of the electronic world, the public questions whether electronic transactions held in electronic systems can protect their rights as consumers. How Islamic Law and Government Regulation No. 82 of 2012 on the Implementation System and Electronic Transactions can be set, and protect the rights of consumers who transact in e-commerce? The method used is the type of normative juridical research, the research focused on reviewing the application of the rules or norms of positive law. Results of the discussion are: e-commerce, can make consumers impressed and interested in buying goods that are marketed. It also became one of the reasons consumers prefer to shop via the Internet. But ignorance of the agreement in e-commerce transactions is as proof of legal agreements often make prospective customers do not dare to carry out a transaction and choose to cancel the transaction because it feels it will be very detrimental and cannot be prosecuted if the business actor defaults or is against the law. So in this paper we will discuss how the laws and regulations relating to ITE can protect the rights of consumers in e-commerce purchases.Keywords: Islamic Perspective,Consumer Protection, E-Commerce Transactions